Burned-Out: Middle School Teachers After One Year of Online Remote Teaching During COVID-19 - Gutentag, Tony; Asterhan, Christa S. C. (Frontiers in Psychology, 2022)
During the height of the COVID-19 pandemic, teachers around the globe had been forced to move their teaching to full-time online, remote teaching. In this study, we aimed at understanding teacher burnout during COVID-19. We conducted a survey among 399 teachers at the peak of a prolonged physical school closure. Teachers reported experiencing more burnout during (vs. before) the COVID-19 pandemic. Contributing factors to this burnout were high family-work conflict and low online teaching proficiency. Burnout was associated with lower work-related well-being: Lower work commitment, and higher turnover intentions. It was also associated with lower psychological well-being: More depressive and anxiety symptoms, and lower subjective well-being. Approach (but not avoid) coping strategies served as a protective factor against the burnout-turnover intentions association. We conclude with recommendations on how to mitigate teacher burnout, thereby contributing to teacher well-being.